Investigation and Comparative Analysis of Natural Moulding Sands from Five Deposits in Maiduguri, Nigeria - Mohammed A. GANA; Zaka A. MSHELIA; Isuwa S. AJI; Alhaji GUJJA; Lawan A.M. KOLO (FUDMA Journal of Engineering and Technology, 2025)
This study investigates foundry sands from samples deposits (A-E) to evaluate their uses for casting applications. Key properties analysed included chemical content, clay content, grain distribution (AFS-GFN), moisture content, bulk density, permeability, compression strength (CS), and refractoriness. Chemical analysis revealed high silica content (68.10% - 79.56% SiO₂) and aluminium oxide (2.68% - 20.52% Al₂O₃), meeting standards for aluminium casting. Impurities like FeO were present but within tolerable limits. Clay content varied significantly (11% - 44.5%), aligning with requirements for non-ferrous metals and specific ferrous alloys. Sieve analysis showed well-graded sands with a high percentage of fine grains (28.84% - 44.2% retained on the 63μm sieve), beneficial for surface finish. AFS-GFN values (60.55 - 90.5) were generally within the recommended range (35-90) for non-ferrous metals. Moisture content (1.9% - 5.6%) was suitable for low-temperature aluminium casting, with permeability (80.1 - 89.1) and Green Compression Strength (60.2 - 71.5 kN/m²) fell within acceptable foundry ranges of. Refractoriness was high (1350°C – 1450 °C), indicating adequate thermal stability. The natural sands, particularly samples A, C, and D, possess suitable physico-chemical properties with high silica, adequate refractoriness with appropriate permeability, and strength for casting practice, especially for non-iron metals and specific ferrous alloys like light grey iron. Sample B’s higher fines content and lower GFN suggest for small-scale and high precision casting.